A Study of Multi-Item Inventory Replenishment Model with Supplier Discounts - Salinas Garza, Nataly Grace / NG (2016)
Some suppliers may offer different types of discounts to incentivise buyers to increase the purchasing order size. Offering discounts is a method of coordination between the seller and the customer (Hwang & Wu, 2013), where the buyer may have to accept specific concessions like acquiring bigger volumes of items, placing the orders at specific points of time or accepting delayed products. These concessions are translated into higher costs for the buyer in various supply chain stages. Therefore, the supplier compensates these costs increment by offering a decrease in the cost per unit in the form of discounts with conditions for the purchaser and supplier. The main objectives of this dissertation are the following: (i) Analyse and describe the key features of the different types of discounts that a supplier might offer. (ii) Identify and explain the Literature Review of the discounts presented. (iii) Create a simple model that is easily implemented and understandable and can give us useful insights about the Multi-Item Inventory Replenishment Model with “bundle” and “quantity” discount. Both “quantity” and “bundle” discounts are present in the industry and service sector. The “quantity” discount offers units at a lower price, if these are purchased in quantities bigger than an established “price break” (Cha & Moon, 2005). While “bundle” discount includes in one package, two or more products or services at a combined attractive price, which is cheaper compared to when purchasing the products separately. By comparing both discounts analysed in the model, it was determined that the success behind “bundle” discount is that it establishes a relation between the sales of each product, while the “quantity” discount is attractive for buyers who are interested in only one type of product or do not require the items included in the bundle package. Hence, the acquisition of more products than the demand is more probable with bundle discount than quantity discount.